Anticoagulation therapy and clinical outcomes in patients with recently diagnosed atrial fibrillation: Insights from the ARISTOTLE trial. (15th January 2017) - Guimarães, Patrícia O.; Wojdyla, Daniel M.; Alexander, John H.; Thomas, Laine; Alings, Marco; Flaker, Greg C.; Al-Khatib, Sana M.; Hanna, Michael; Horowitz, John D.; Wallentin, Lars; Granger, Christopher B.; Lopes, Renato D.
Abstract: Background: Evidence supporting use of antithrombotic therapy in atrial fibrillation (AF) is based mainly on data from patients with permanent, persistent, or paroxysmal AF. Less is known about the risk following a new diagnosis of AF and the efficacy and safety of apixaban in these patients. Methods: Using data from ARISTOTLE, we assessed the relationship between timing of AF diagnosis and clinical outcomes and the efficacy and safety of apixaban versus warfarin in these patients. Recently diagnosed AF was defined as a new diagnosis of AF within 30 days prior to enrollment. Cox proportional hazards models were used to determine the association between recently diagnosed AF and clinical outcomes. We also assessed the efficacy and safety of apixaban versus warfarin according to time since AF diagnosis. Results: In ARISTOTLE, 1899 (10.5%) patients had recently diagnosed AF. After adjustment, patients with recently versus remotely diagnosed AF had a similar risk of stroke/systemic embolism (HR = 1.07, 95% CI = 0.80–1.42; p = 0.67), but higher mortality was seen in patients with recently diagnosed AF (adjusted HR = 1.21, 95% CI = 1.02–1.43; p = 0.03). The beneficial effects of apixaban, compared with warfarin, on clinical outcomes were consistent, irrespective of timing of AF diagnosis (all interaction p -values > 0.12). Conclusion: Patients with recently diagnosed AF had a similar risk of stroke but higher mortality than patients with remotely diagnosed AF, suggesting that they are not at "low risk" and warrant stroke prevention strategies. The benefits of apixaban over warfarin were preserved, irrespective of timing of AF diagnosis.